METHODOLOGY FOR ASSESSING THE ENERGY EFFICIENCY OF HEAT-TECHNOLOGICAL EQUIPMENT FOR OIL AND GAS PROCESSING INDUSTRIES - Nodirbek Rustambekovich Yusupbekov; Shukhrat Manapovich Gulyamov; Nasiba Djumabayevna Xodjiyeva; Yusuf Shodiyevich Avazov; Bakhodir Akilovich Sharipov (International Engineering Journal For Research & Development, 2022)
Based on the analysis of the current state of the theory and practice of deep processing of hydrocarbon raw materials, the relevance and relevance of developing a methodology for assessing the energy and resource efficiency of heat-technological devices and installations with the introduction of the efficiency coefficient Ke, which allows taking into account not only the thermodynamic characteristics of the heat-technological system, but also the design characteristics of the studied technological structure, is shown. It is shown that the use of the considered technique in the development of optimal energy-saving systems can significantly reduce energy consumption.